1999
DOI: 10.1177/10778019922181473
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence in the Vietnamese Immigrant Community

Abstract: This study examines domestic violence in Vietnamese American families, focusing on changes in socioeconomic structure and culture, to identify factors associated with wife abuse. Husbands' patriarchal beliefs and dominant positions in the family and conflicts about changing norms and values between husbands and wives were found to be related to wife abuse. The study suggests that class, culture, gender, and immigration status could simultaneously affect women's experience of violence by husbands. For Vietnames… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
1
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 23 publications
7
148
1
4
Order By: Relevance
“…These feelings of loyalty and hesitancy to step outside the boundaries of traditional family and cultural norms are similar to those experienced by other immigrant survivors, and they are a continual barrier to help-seeking (Bui & Morash, 1999;Dasgupta & Warrier, 1996;Yoshioka et al, 2001).…”
Section: Availability Of Supportmentioning
confidence: 88%
“…These feelings of loyalty and hesitancy to step outside the boundaries of traditional family and cultural norms are similar to those experienced by other immigrant survivors, and they are a continual barrier to help-seeking (Bui & Morash, 1999;Dasgupta & Warrier, 1996;Yoshioka et al, 2001).…”
Section: Availability Of Supportmentioning
confidence: 88%
“…These results coincide with Adam (2000), who reported a higher percentage of psychological abuse compared to other forms of abuse within the past year in a sample of South Asian women, and with Thapa-Oli et al (2009) who reported that 54 % of the women in their more recent study of Nepali immigrant women in the U.S. suffered psychological abuse. Psychological abuse varies from male control over family decision-making (Bui and Morash 1999) to verbal abuse and insults to women, especially in front of others, leading to humiliation, and ridiculing of their looks, cooking ability, and other qualities (Supriya 1995;Raj and Silverman 2002). These manifestations were also found among the women in the current study who reported psychological abuse in the past year.…”
Section: Extent Of Abusementioning
confidence: 97%
“…Some  RESEARCH AND PRACTICE  26 Other studies have suggested that postmigration stresses, such as poverty, underemployment, loss of status, and discrimination, affect the power dynamics between men and women and thus, increase women's risk for IPV. [27][28][29] Alternate explanations do not relate to behavioral or social determinants but rather reflect changing perceptions and interpretations of IPV as newcomers learn what acts constitute abuse in the context of the adopted country and develop the language skills necessary for identifying and speaking about their experiences. If so, then previous cultural norms of what is considered abusive behavior change over time to accommodate new constructs, which may result in higher reported rates of IPV.…”
Section: Discussionmentioning
confidence: 99%